Determination of single embryo sex in Macaca mulatta and Mus musculus RNA-Seq transcriptome profiles - Midic, Uros (Physiol Genomics, 2018)
To account for sex as a biological variable, it is sometimes necessary to identify the sex of an embryo or embryonic cell that was used to generate libraries for RNA sequencing, without the sex being known a priori. The preferred approach for this would take advantage of the mRNA data, rather than relying on other methods that require separation and analysis of genomic DNA or diversion of limiting RNA for other assays. We describe here a method that has been optimized for this purpose in samples of rhesus monkey and mouse embryos. This method is broadly applicable to any species for which a sufficiently well characterized genome and knowledge of polymorphisms are available, and for embryos that are transcriptionally active and expressing their genome.